Error Analysis of English Lexical Collocation Translated By Students of the English Literature - Egris Dain; Arman Arman (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2020)
The objective of this study was to know whether the students made errors or not and to explain the mostly the students made errors in translation lexical collocation of their written test. The kinds of errors in this study were divided into five categories; inversion, addition, omission, modification, and deviation. In this study, the researcher used a descriptive qualitative method to describe students’ errors. The data which was taken from the written test focused on translation lexical collocation consist of five-point which is adjective+ Noun, Noun+ Noun, Verb+ Noun, Noun+ Verb, and Verb+ adverb with five lists of sentences. The subject of this study is the students of the English literature faculty of humanities Universitas Halu Oleo, Academic Year 2017/2018, and took the Translation subject. The researcher took one class that consisted of 18 students. The findings showed errors that there were 80 errors made by students. Based on the result, it shows that the researcher found the students made errors of Inversion of meaning (50 errors), Addition of meaning (12 errors), Omission of meaning (6 errors), Deviation of meaning (1 error), and Modification of meaning (11 error). The conclusion of this study was the English literature students faculty of humanities Universitas Halu Oleo, still made all kinds of errors in translation lexical translation; inversion, addition, omission, modification, and deviation.